Intradermal thumbtack needle buried Neiguan (P6) point for prevention of postoperative nausea and vomiting in patients undergoing craniotomy: study protocol for a randomised controlled trial - Jian-qin Lv; Chengwei Wang; Yu Li; Tian-hao Xu; Ling-qi Jian (BMJ Open)
Introduction Postoperative nausea and vomiting (PONV) is among the most common adverse reactions following anaesthesia and surgery. Recent clinical studies have reported that the average incidence is about 30%, while in patients specifically undergoing neurosurgery, the incidence can be as great as 73%. Studies also suggest that its occurrence increases the risk of intracranial haematoma and haemorrhage. The objective of this study is to evaluate the effectiveness of intradermal thumbtack needle buried Neiguan (pericardium 6 (P6)) point therapy in the prevention of PONV in patients undergoing craniotomy under general anaesthesia.Methods and analysis This is a single-centre, three-arm, randomised controlled trial. 180 participants are randomly assigned to either an acupuncture, intradermal thumbtack needle or control group in a 1:1:1 ratio. The P6 of the acupuncture group is punctured at both sides perpendicularly to a depth of 20 mm. Needles are retained for 30 min and stimulated every 10 min to maintain the de qi. The therapy includes two treatments; the acupuncture is administered immediately after and 24 hours after surgery. For the intradermal thumbtack needle group, the intradermal thumbtack needle is quickly inserted into the skin and embedded at P6 acupoints bilaterally. Patients and their families are asked to press the needlepoint with the onset of nausea, vomiting, bloating, pain and other reported discomforts. The needle is replaced after 24 hours. The therapy is administered immediately after and 24 hours after surgery. For the control group, no intervention is carried out. The incidence of PONV within 48 hours after craniotomy across the three groups is observed. Other observations include: (1) assessment of nausea score (severity of nausea) and pain score (visual analogue scale) 0–2, 2–6, 6–24 and 24–48 hours after craniotomy under general anaesthesia; (2) assessment of total rescue antiemetic dosage 0–48 hours after craniotomy under general anaesthesia; (3) length of hospital stay and (4) patient satisfaction score with PONV management. We will perform all statistical analysis following the intention-to-treat principle.Ethics and dissemination Ethics approval has been granted by the Bioethics Subcommittee of the West China Hospital, Sichuan University: the approval number is 2018 (number 231). Results will be expected to be published in peer-reviewed journals.Trial registration number ChiCTR1800017173